Novel emissions prevention process for regulating process emissions for better protection of the environment and public health - William Ejuvweyerome Odiete (Results in Engineering)
The present global industrial practice of regulating targeted pollutants in process emissions through treatment and releasing the non-targeted pollutants untreated into the atmosphere is not good for protection of the environment and public health. The aforesaid led this work to invent the “Novel Emissions Prevention Process for Regulating Process Emissions” to be applied alongside the treatment for better protection of the environment and public health. It hinges on the concept of maximum allowable pollution load and the novel concept of cooperative compliance to environmental regulations. It reduces the pollution load of process emissions at source. The research methods applied include, mathematical modeling, questionnaire survey, use of published experimental data and design. Results showed that pollution load is a measure of environmental damage caused by process emissions. Results revealed that pollution load should be regulated alongside treatment of process emissions. Results showed that a country can achieve up to greater than 99 % reduction in its original pollution load of process emissions upon adoption of the novel emissions prevention process. Results showed that, the novel emissions prevention process enables treated process emissions of higher quality than presently released by industry into the environment. Results revealed that industry can apply the novel emissions prevention process to determine the production rate of finished goods corresponding to the prevention pollution load of process emissions for better protection of the environment and public health. The novel emissions prevention process has global applicability. It can be applied in every country.